COMPLEX MODEL SYSTEMS AND TECHNICAL SERVICE OF AVIATION TECHNOLOGY - Тамаргазін, O. A. (Proceedings of National Aviation University (archive), 2020)
The basic principles of constructing a model of the maintenance system of compressed airborne vehicles operating on the state are considered. The main characteristics of the model and their influence on the probability of aviation equipment being in a state are analyzed.readiness to use